Integrated Adaptation Approaches to Climate Change in Semi-arid Basin of Iran - Solaymani, Hamid R; Gosain, A K (Annals of Arid Zone, 2019)
The major challenges concerning freshwater include: experiencing extremes of too much and/or, too little water, and consequent water issues. Each of these problems may be intensified by climate change in semi-arid areas. Existing research and observational evidence provide strong arguments that future climate may change significantly and, therefore, impact the water resources of the Karkheh basin of Iran. Thus, the strategies that can be used to mitigate possible negative impacts of climate change on water resources are of great importance. The risk of drought and heat stress is expected to increase in the whole of the study area. Overall, the present study shows the consequences of climate change on the water resources of the Karkheh Basin and shall be useful in formulating the adaptation options in a sustainable manner. SWAT model was used for impact assessment analysis by using the future climate scenario with future regional climate models. It has been found that there shall be an explicit deficit in water as well as crop yield during the end of the century. The impact of suggested adaptation activities had various effects on hydrology and the same has been depicted through tracking major hydrological components; e.g. surface runoff, groundwater and sediment erosion. Amongst the suggested adaptation scenarios, activities that include terracing, strip cropping, Grade Stabilization Structure (GSS), and contouring were found to influence the desired hydrologic components significantly. The land use and cropping pattern changes were also successful in bringing about the desired changes to the hydrologic components. Key words: Adaptation, crop pattern, land use, Karkheh Basin, SWAT model.